The new population problem : why families in developed countries are shrinking and what it means - Booth, Alan, 1935-2015; Crouter, Ann C. (Penn State University family issues symposia series., 2005)
This book is based on the presentations and discussions from a national symposium on "Creating the Next Generation: Social, Economic, and Psychological Processes Underlying Fertility in Developed Countries," held at the Pennsylvania State University in 2003.